Ainu Art: From Craft to Fine Art - Marina V. Osipova (Гуманитарный вектор)
In modern scientific literature there is a lack of works on the new forms of Ainu art, which is considered as traditional and utilitarian. The modernity gives the boost to the development of the new forms of art. However, there are no studies in domestic or foreign historiography examining this issue. The purpose of this article is to analyze the problem of the formation and development of Ainu modern art as the adaptive mechanisms of traditional crafts. Based on field work and analysis of sources, using descriptive, historical-systemic, comparative-historical and visual methods, an attempt is made to understand the prerequisites for the transition of Ainu craft and decorative art to fine arts, and the conditions that led to the emergence of highly artistic works. The introduction of the results determined the novelty of this research. We found that the transition of the Ainu crafts to decorative and fine arts was facilitated by three factors: economic, cultural and the need for individual self-identification. This made possible to distinguish three stages in the development of Ainu art: the stage of acquaintance with the Ainu craft, the exhibition and market stages, which led to the development of sculpture, graphics, woodcuts and also to emphasize the importance of cultural exchange with neighboring peoples. The presented work allows us to conduct comparative studies with a similar phenomenon among the indigenous peoples of the Russian Federation and to use it in museum projects.